Scanning probe microscopy study of chemical vapor deposition grown graphene transferred to Au(111). (December 2015) - Schouteden, K.; Galvanetto, N.; Wang, C.D.; Li, Z.; Van Haesendonck, C.
Abstract: Graphene is grown by chemical vapor deposition (CVD) on copper films and transferred ex situ to atomically flat Au(111) films, after which the sample is annealed in ultra-high vacuum (UHV) prior to scanning tunneling microscopy (STM) investigation. STM imaging at 78 K reveals large, clean and defect-free atomically flat areas that are separated by graphene wrinkles and grain boundaries. In addition to the graphene atomic structure, the flat surface regions exhibit patterns with larger periodicity that can be interpreted as Moiré patterns formed by the atomic lattices of the graphene and the gold. Our findings show that the CVD growth and ex situ transfer of graphene (G) to atomically flat Au(111) surfaces allows obtaining clean and high-quality G/Au surfaces that are suitable for in situ deposition of, e.g., molecules and atoms, for UHV investigation purposes. This approach may offer a higher degree of freedom in preparing bare and doped graphene on atomically flat surfaces compared to a full in situ approach. Graphical abstract: Description: Three-dimensional perspective view of an atomically resolved scanning tunneling microscopy image of single-layer graphene (SLG) on Au(111). The SLG is grown by chemical vapor deposition on a copper foil and is subsequently transferred to the Au(111) substrate. The long-rang commensurability of the SLG and Au atomic lattices gives rise to the appearance of Moiré patterns, which thereby evidence the high quality of the SLG/Au surface. Fourier-filtering was applied to further optimize the experimental image.